2019
DOI: 10.1002/jbm.a.36653
|View full text |Cite
|
Sign up to set email alerts
|

Potential core–shell designed scaffolds with a gelatin‐based shell in achieving controllable release rates of proteins for tissue engineering approaches

Abstract: The biomaterials design as core–shell structures opens a new door to the release of susceptible biomolecules in a controllable manner and enables to place natural biomaterials as shell layers to impart the effective biofunctional features at surfaces. In this study, core–shell designed scaffolds were prepared using coaxial electrospinning with hybrid of gelatin (GT)/polycaprolactone (PCL) at different weight ratios as their shell and protein solution as their core, followed by cross‐linking to impart controlla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 74 publications
1
14
0
Order By: Relevance
“…The range between three groups was able to be tailored with the maximum variation of 1 lm. Some studies reported similar findings that addition of biomolecules results in thinner fibres [14,23].…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…The range between three groups was able to be tailored with the maximum variation of 1 lm. Some studies reported similar findings that addition of biomolecules results in thinner fibres [14,23].…”
Section: Discussionsupporting
confidence: 53%
“…Recently evidence has shown the advantages of protein addition into polymeric scaffolds, with the desired outcome and response due in part to its composition, binding method and presentation [12,13]. However, a major challenge is to preserve the bioactivity, which is important in maintaining cell attachment and behaviour [14,15]. Also additional characteristics can be inadvertently effected by washing and sterilization steps which could cause damage or removal [16,17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wound dressings consisting of electrospun nanofibers mesh made of natural, semi‐synthetic, and fully synthetic polymers have been used. Gelatin, a natural polymer, is widely used in combination with other synthetic biodegradable polymers such as PCL, 113,123,131 Poly(lactide‐co‐ε‐caprolactone), 122 PLA, 126 PVA, 147 and cellulose acetate 117 to create bioinspired nanofibers for in vitro as well as in vivo wound healing applications. Incorporation of gelatin in nanofibers promotes fibroblasts and keratinocytes attachment, migration, and proliferation, as well as the essential ECM components secretion such as collagens in vitro and speeds up wound healing in vivo due to its fascinating cell‐favorable biological features such as biocompatibility, biodegradability, and bioactivity.…”
Section: In Vitro and In Vivo Advancements Of Nanofibers In Wound Healing Applicationsmentioning
confidence: 99%
“…20,21 However, since the elasticity of PLCL electrospun fibrous matrices reduces after gamma-ray irradiation and in order to improve cellular interactions with the PLCL fibrous scaffold, a small amount of gelatin (GE) was blended with the PLCL in order to alter the surface hydrophobicity. 5,22 GE is a valuable protein for biomedical industries. Natural biopolymers such as GE and collagen have beneficial effects on biological recognition signals and improve the adhesion, spreading and proliferation of cells remarkably.…”
Section: Introductionmentioning
confidence: 99%